Plasmodium ovale Infection After One Year Mefloquine Prophylaxis in A Young Indonesian Soldier: A Case Report - Frans Liwang; Dewi Mira Ratih; Soroy Lardo (Acta Medica Indonesiana, 2019)
Malaria chemoprevention using mefloquine has become the WHO standard regimen for military personnel who stay in the endemic area for an extended period of time. We reported a case of Plasmodium ovale infection in a young Indonesian Soldier following one year mefloquine prophylaxis 250 mg weekly. Typical fever and chills were experienced two weeks after returning from one year duty in Congo, West-Central Africa. The diagnosis of ovale malaria was made by peripheral blood smear, and 35/250 parasites in small microscopic view was found. Then, he recovered after dihydroartemisin and primaquine combination therapy. This was an unusual case of long-term prophylaxis failure since mefloquine has been recognized as the agent for malaria prevention, even multi-drug-resistance Plasmodium. Dormant stage of Plasmodium ovale, quinoline-resistance potential, and the efficacy of mefloquine itself are discussed as the cause of that phenomenon.